Literacy and Clean Living Habit Model Through the Character Education Pillar Program for Early Childhood - M. Iqbal Tawakkal; Sulistyowati (CV. AGRAPANA MEDIA, 2026)
This study aims to analyze the model of literacy habituation and clean living through the character education pillar program implemented at RA Fattahul Huda Pungpungan. Character education is an important aspect of early childhood education to shape attitudes, behavior, and positive values in students. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the character education pillar program is implemented through two main activities, namely the literacy pillar and the clean living pillar. The literacy pillar includes activities such as reading storybooks and reading books in the reading corner, which can increase reading interest and help students understand moral values. Meanwhile, the clean living pillar includes activities such as queuing to wash hands and maintaining personal and environmental cleanliness. The activity is carried out routinely as a form of habituation in daily school activities. The implementation of this activity aligns with Thomas Lickona's character education theory, which includes moral knowing, moral feeling, and moral action. Through continuous habituation, students are able to develop an interest in reading, discipline, responsibility, as well as clean living habits.